Publishing in an electronic age: prospects and challenges (2018)
Publishing, from inception till date, has transited through different stages courtesy of technological discoveries and inventions. From the invention of printing machine by Johan Gutenberg in Germany, technology has continued to revolutionise printing and influenced publishing generally. With technological advancement, the publishing profession is heavily electronic oriented with virtually all its activities from manuscript sourcing to productionelectronic-driven. Publishing has no doubt arrived at electronic age. Though electronic publishing is novel and resourceful, it is not without its challenges. The issue of prospects and challenges of electronic publishing therefore constitute the focus of this paper. The paper examines the conventional publishing processes which follows a Content -Aggregation - Production-Marketing-Distribution -Sale-Consumption continuum as against Electronic (digital) publishing which maintains Content - Aggregation - Marketing - Sale - Consumption sequence. The paper also examines the prospects and challenges of electronic publishing and round-off with conclusion.